Long-term development of performance, physiological, and training characteristics in a world-class female biathlete - Solli, Guro Strøm; Flom, Andrine Håstul; Talsnes, Rune Kjøsen (Frontiers in Sports and Active Living, 2023)
Purpose: To investigate the long-term development of performance, physiological, and training characteristics in a world-class female biathlete, with emphasis on differences between junior and senior athlete seasons. Methods: The participant is a highly decorated female biathlete with 22 (10 gold) medals from international championships and 28 individual World Cup wins. Performance development (age 17-33), physiological tests (age 22-33), and day-to-day physical and shooting training (age 17-33) were analyzed. Training data was systemized by endurance (low- [LIT], moderate- [MIT], and high-intensity training [HIT]), exercise mode, and strength training. Shooting training recorded for each session included the number of shots fired during rest, LIT, MIT, HIT, or competitions, and time spent on dry-fire training. Results: The annual volume of physical training (409 to 792 h·season-1) and number of shots fired (1163 to 17328shots·season-1) increased from age 17-28 followed by a subsequent reduction in physical training (range 657–763 h·season-1) and shots fired (13275-15355shots·season-1) during the seasons of peak performance at age 31-33. Maximal oxygen uptake in roller-ski skating increased by 10% (62.9 to 69.2 ml·kg-1·min-1) from age 22-27. The physical training volume was 48% higher (694±60 vs. 468±23 h·season-1,P=.030), with 175% more shots fired (14537±1109 vs. 5295±3425shots·season-1, P=.016) as senior than junior athlete. In the physical training, these differences were mainly explained by higher volumes of LIT (602±56 vs. 392±22 h·season-1,P=.032) and MIT (34±1 vs. 7±2 h·season-1,P=.001) but less HIT (27±1 vs. 42±3 h·season-1,P=.006) as a senior than junior. In line with this, the shooting training as senior included more shots fired both at rest (5035±321 vs. 1197±518 shots·season-1,P=.011) and during LIT (7440±619 vs. 2663±1975 shots·season-1,P=.031), while a smaller insignificant difference was observed in the number of shots fired in connection with MIT, HIT, and competitions (2061±174 vs. 1435±893 shots·season-1,P=.149). Conclusions: This study provides unique insights into the long-term development of physical and shooting training from junior to senior in a world-class female biathlete. The major differences in training characteristics between junior and senior athlete seasons were higher sport-specific volumes of LIT and MIT, and less HIT. These differences were accompanied by more shooting training, particular at rest, and in connection with LIT.